Pelanggaran Usaha Neynis Food Ditinjau dari Peraturan Menteri Pasal 4 Ayat (1) Peraturan Pemerintah Nomor 42 Tahun 2007 Tentang Waralaba Ditinjau dari Aspek Kepastian Hukum - Syaeh, Muhammad Tunjang; Syahputra, Fajar Dwi; Mohamad, Syafa Fattah; Tjokronolo, Nabil Raditya; Ramadhani, Dwi Aryanti (Media Hukum Indonesia (MHI), 2024)
A franchise is a business system that involves two parties, namely the Franchise Owner (franchisor) and the Franchisee (franchisee), where the Franchise Owner grants licensing rights to the Franchisee based on a written agreement. In order for a business to be categorized as a franchise, the business must meet several criteria, including registering a franchise agreement prospectus and having a Franchise Registration Certificate. However, in the case of Neynis Food, the business has not registered its franchise with the state even though it has claimed to be a franchise business. This research aims to analyze the legal consequences if the Franchise Owner does not register their business, as well as legal protection for the Franchisee. This research uses normative juridical methods, which examine the laws that apply in society and their application in practice. The research results show that the Neynis Food business does not meet the requirements to be categorized as a franchise, and if it continues to claim so, the business can be considered illegal because it does not comply with the provisions in Minister of Trade Regulation No. 71 Years 2019.